2010
DOI: 10.1111/j.1532-5415.2010.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Volume and Survival from Age 78 to 85: The Contribution of Alzheimer‐Type Magnetic Resonance Imaging Findings

Abstract: RESULTS: Thirty-seven of 98 (34.9%) participants died during follow-up. After adjustment for cognitive ability at time of MRI examination, childhood intelligence, sex, hypertension, smoking history, obesity, hyperlipidemia, and age at MRI, proportion of intracranial volume occupied by the brain (brain fraction) predicted death before age 85 (P 5.04). Participants with brain fraction less than 0.726 had more than twice the relative risk (2.8, 95% confidence interval 5 1.1-7.3) of death than participants with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…In the present study, lower brain weights were associated with better survival consistent with a gradual loss of brain volume in FTLD-TDP with disease progression. By contrast, in one study of AD, poorer survival was associated with lower gray matter volume, and smaller volume reductions in brain predicted better survival [56].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, lower brain weights were associated with better survival consistent with a gradual loss of brain volume in FTLD-TDP with disease progression. By contrast, in one study of AD, poorer survival was associated with lower gray matter volume, and smaller volume reductions in brain predicted better survival [56].…”
Section: Discussionmentioning
confidence: 95%
“…Small vessel disease (SVD) is an incidental but frequent finding on brain scans of elderly individuals (Vermeer et al 2003;resonance tomography (MRI) by the brain imaging markers white matter lesions (WML) and lacunar infarcts (LI). While brain MRI has become a frequently used diagnostic tool, also in population-based epidemiologic studies, only few studies have examined the impact of structural brain changes on survival in elderly populations (Briley et al 2000;Bokura et al 2006;Kuller et al 2007;Ikram et al 2009;Staff et al 2010;Olesen et al 2011;Conijn et al 2011). In these studies, global vascular brain lesions and brain atrophy were associated with an increased risk of mortality in the elderly.…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, brain atrophy is associated with cognitive decline in other situations in which there is no obvious initial brain injury. 30,37 It is possible that brain volumes changed due to changes in brain blood volumes. Finally, the clinical relevance of these findings is unknown and uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…8,31,36 The magnitude of the changes in brain volume was small, but it is in the ranges measured reproducibly in other studies and that were of clinical importance. 7,30,37 Brain volumes decreased approximately 0.3% per year in healthy aging humans. 28 Another study found smokers with cognitive impairment had significantly smaller gray matter volumes, with differences between groups of less than 5%.…”
Section: Discussionmentioning
confidence: 99%